2021
DOI: 10.1108/ijesm-04-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of environmental degradation in Saudi Arabia: exploring the unexplored

Abstract: Purpose Environmental degradation is recognized as a serious problem globally, and hence, Saudi Arabia is no exception. This paper aims to focus on the economy of Saudi Arabia to identify the determinants of environmental degradation. Design/methodology/approach Time series data spanning from 1971 to 2014 is used and analyzed using the recently developed autoregressive distributed lag modeling approach. Findings The obtained results reflected that natural resources, per person income and urbanization, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Concern for environmental protection has led private and public organizations to invest heavily in research on new technologies to generate energy from renewable sources (Ellabban et al , 2014; Fusco et al , 2017; Tahir et al , 2021). Renewable energy sources contribute to achieving two major objectives in modern society: reducing greenhouse gases by curbing the impacts of climate change; and guaranteeing the security and reliability of energy supplies in the long term without the possibility of depletion (Banos et al , 2011; Elumalai et al , 2021; Anil et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concern for environmental protection has led private and public organizations to invest heavily in research on new technologies to generate energy from renewable sources (Ellabban et al , 2014; Fusco et al , 2017; Tahir et al , 2021). Renewable energy sources contribute to achieving two major objectives in modern society: reducing greenhouse gases by curbing the impacts of climate change; and guaranteeing the security and reliability of energy supplies in the long term without the possibility of depletion (Banos et al , 2011; Elumalai et al , 2021; Anil et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Concern for environmental protection has led private and public organizations to invest heavily in research on new technologies to generate energy from renewable sources (Ellabban et al, 2014;Fusco et al, 2017;Tahir et al, 2021). Renewable energy sources contribute to achieving two major objectives in modern society:…”
Section: Introductionmentioning
confidence: 99%
“…Still, others found that trade openness does not impact environmental degradation, like Ayobamiji and Kalmaz (2020), Shah et al. (2022) and Tahir et al. (2022).…”
Section: Recent Literature Reviewmentioning
confidence: 97%
“…,Nguyen et al (2018),Karasoy and Akçay (2019),Ansari et al (2020),Kongbuamai et al (2020),Burki and Tahir (2022),Roy (2023) andWang et al (2023). Still, others found that trade openness does not impact environmental degradation, likeAyobamiji and Kalmaz (2020),Shah et al (2022) andTahir et al (2022).…”
mentioning
confidence: 98%
“…Several attempts have been made in the literature to uncover the causes of environmental pollution, with conflicting results (Mesagan and Nwachukwu, 2018;Omri et al, 2019;Shaheen et al, 2020;Ur Rehman and Zeb, 2020;Chien et al, 2021;Khalid et al, 2021;Rjoub et al, 2021;Tahir et al, 2021;Burki and Tahir, 2022;Chu, 2022). Undoubtedly, the extant studies have identified numerous factors including economic and demographic factors as drivers of environmental degradation.…”
Section: Introductionmentioning
confidence: 99%